Recombinant Sialyltransferase Infusion Mitigates Infection-Driven Acute Lung Inflammation - Nasirikenari, Mehrab; Lugade, Amit A.; Neelamegham, Sriram; Gao, Zhongwei; Moremen, Kelley W.; Bogner, Paul N.; Thanavala, Yasmin; Lau, Joseph T. Y. (Frontiers in Immunology, 2019)
Inappropriate inflammation exacerbates a vast array of chronic and acute conditions with severe health risks. In certain situations, such as acute sepsis, traditional therapies may be inadequate in preventing severe organ damage or death. We have previously shown cell surface glycan modification by the circulating sialyltransferase ST6Gal-1 regulates de novo inflammatory cell production via a novel extrinsic glycosylation pathway. Here, we show that therapeutic administration of recombinant, bioactive ST6Gal-1 (rST6G) mitigates acute inflammation in a murine model mimicking acute exacerbations experienced by patients with chronic obstructive pulmonary disease (COPD). In addition to suppressing proximal neutrophil recruitment at onset of infection-mediated inflammation, rST6G also muted local cytokine production. Histologically, exposure with NTHI, a bacterium associated with COPD exacerbations, in rST6G-treated animals revealed consistent and pronounced reduction of pulmonary inflammation, characterized by smaller inflammatory cuffs around bronchovascular bundles, and fewer inflammatory cells within alveolar walls, alveolar spaces, and on pleural surfaces. Taken together, the data advance the idea that manipulating circulatory ST6Gal-1 levels has potential in managing inflammatory conditions by leveraging the combined approaches of controlling new inflammatory cell production and dampening the inflammation mediator cascade.